ACCESS PROVISIONS UNDER THE RTE ACT (2009) AND SSA - Rekha, Chiter (THE PRIMARY TEACHER, 2011)
The National Policy on Education (NPE) 1986/92, which stands as a major landmark in the country’s journey towards Universal Elementary Education (UEE) states: “In our national perception, education essentially for all… Education has an acculturating role. It refines sensitivities and perceptions that contribute to national cohesion, a scientific temper and independence of mind and spirit thus furthering the goals of socialism, secularism and democracy enshrined in our Constitution.” With the formulation of NPE, India initiated a wide range of programmes for achieving the goal of UEE. These efforts were intensified in the 1980s and 1990s through several schematic and programme interventions, such as Operation Black Board, Shiksha Karmi Project, Andhra Pradesh Primary Education Project, Bihar Education Project and SSA after 2001.